2019
DOI: 10.1177/1098611119873332
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by Cop: A New Perspective on an Old Phenomenon

Abstract: Suicide by cop (SbC) occurs when an individual purposely engages in threatening behavior toward police officers in an attempt to be killed. Previous studies have found the prototypical SbC subject is male, mid-30s, with disrupted relationships, and mental health concerns, although these studies have almost exclusively relied on officer involved shootings or public information as sources of data. To address the dearth of knowledge for SbC cases involving no force or less lethal force, 419 SbC cases from the Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Beyond studies centered on examining potential race or ethnicity effects, researchers have also looked at a host of additional factors. Scholars have found that in police-citizen encounters in which a subject is armed with a gun or weapon and an officer is injured, the likelihood of officer-involved shootings (Davies, 2017; Jordan et al, 2020; Morgan et al, 2020; Taylor, 2020; Wheeler et al, 2018; Worrall et al, 2018), the number of shots fired by the police officer (White & Klinger, 2012), and the lethality of an officer-involved shooting (Fridel et al, 2020; Jennings et al, 2020; Johnson et al, 2019), all significantly increase. Researchers have also found a significant positive association between officer-involved shootings and police officers with prior police misconduct or citizen complaints (Kargin, 2016; Ridgeway, 2016; Worrall et al, 2018; Zhao & Papachristos, 2020), police militarization (Lawson, 2019), levels of household gun ownership (Hemenway et al, 2019), mental illness (DeGue et al, 2016; Lord, 2014), and Western states (Helms & Costanza, 2020; Johnson, 2013; Willits & Nowacki, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond studies centered on examining potential race or ethnicity effects, researchers have also looked at a host of additional factors. Scholars have found that in police-citizen encounters in which a subject is armed with a gun or weapon and an officer is injured, the likelihood of officer-involved shootings (Davies, 2017; Jordan et al, 2020; Morgan et al, 2020; Taylor, 2020; Wheeler et al, 2018; Worrall et al, 2018), the number of shots fired by the police officer (White & Klinger, 2012), and the lethality of an officer-involved shooting (Fridel et al, 2020; Jennings et al, 2020; Johnson et al, 2019), all significantly increase. Researchers have also found a significant positive association between officer-involved shootings and police officers with prior police misconduct or citizen complaints (Kargin, 2016; Ridgeway, 2016; Worrall et al, 2018; Zhao & Papachristos, 2020), police militarization (Lawson, 2019), levels of household gun ownership (Hemenway et al, 2019), mental illness (DeGue et al, 2016; Lord, 2014), and Western states (Helms & Costanza, 2020; Johnson, 2013; Willits & Nowacki, 2014).…”
Section: Resultsmentioning
confidence: 99%